2015
DOI: 10.1007/s10854-015-3974-3
|View full text |Cite
|
Sign up to set email alerts
|

Structure and charge density of Ce doped gadolinium gallium garnet (GGG)

Abstract: Nanocrystalline powders of cerium doped gadolinium gallium garnet (Gd 3 Ga 5 O 12 , GGG) powders were prepared by an aqueous sol-gel method. Effects of Ce doping on the microstructure, band gap energy and electron density distributions of the grown Gd 3-x Ce x Ga 5 O 12 (x = 0.5, 1 and 3) have been studied by means of scanning electron microscopy, diffuse reflectance spectroscopy, X-ray diffraction techniques and the maximum entropy method (MEM). The mid bond densities between different atoms of Gd 3-x Ce x Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…It can be heavier doped with rare-earth ions and has less concentration quenching. 18,19 Cerium ions are efficient luminescence centers in many garnets for the fast fluorescence decay and easy energy transfer. 20 Combining the advantages of the rare-earth ion and the host material, the Ce 3þ ∶GGG crystals show promising applications in high-energy physics, laser materials, and integrated optics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be heavier doped with rare-earth ions and has less concentration quenching. 18,19 Cerium ions are efficient luminescence centers in many garnets for the fast fluorescence decay and easy energy transfer. 20 Combining the advantages of the rare-earth ion and the host material, the Ce 3þ ∶GGG crystals show promising applications in high-energy physics, laser materials, and integrated optics.…”
Section: Introductionmentioning
confidence: 99%
“…The GGG crystal belongs to the cubic system and is a special substrate for magneto-optical thin films for microwave isolators. It can be heavier doped with rare-earth ions and has less concentration quenching 18 , 19 . Cerium ions are efficient luminescence centers in many garnets for the fast fluorescence decay and easy energy transfer 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few decades, the sol-gel technique has been used to prepare a variety of mixed-metal nanoporous oxides, nanomaterials, nanoscale architectures and organicinorganic hybrids [27][28][29][30][31][32]. Previous work has shown that sol-gel process offers considerable advantages such as better mixing of the starting materials and excellent chemical homogeneity in the final product.…”
Section: Introductionmentioning
confidence: 99%